Investigation of Chitosan as Edible Coating on Storage of Star Apple (Chrysophyllum Cainino) Fruit - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Star apple or milk fruit (Chrysophyllum cainino) is a non climacteric fruit and is considered exotic. It has a very pleasant flavor and nice appearance because of its star shape when cut in half. It’s widely cultivated in South of Vietnam. The fruits are shining apple-sized berries. The immature fruits are astringent and contain sticky white latex. The fruit is bright green and greenish-yellow to red violet when ripe, and should be eaten when fully ripe. It has excellent health and medicinal benefits. Despite its food benefits, star apple is highly perishable due to its high moisture content which is susceptible to microbial action. Objective of this study focused on the chitosan edible coating affected to weight loss, protein, total soluble solid, vitamin A and vitamin C in star apple (Chrysophyllum cainino) fruits. Different concentrations of chitosan (0%, 0.25%, 0.5%, 0.75%, and 1%) were examined. Results demonstrated that star apple fruits which were coated with 0.75% chitosan still maintained shelf-life until 15 days of preservation. So the use of chitosan coating was one promising method to improve stability of star apple (Chrysophyllum cainino) fruits during storage and distribution.Keywords: Chrysophyllum cainino, Edible coating, Chitosan, Stability, Storage, distribution.